?EFFECT OF SOME PHYSIOLOGICAL AND BIOCIIIIMICAL Asn:cIS Q.~AomltNml: Bur- TANOL PRODUcnON BY CWSTlUDmM ACErOBrnTUCIJjM - El-Minofy, Hassaan A.; Hamdy, Abd El-Hamid A.; yassine, Mohammad; Amin, Hala A. (Biological Sciences - PJSIR, 2000)
The effect of scmre faJiJ!l.eliIuaIlii(1J1j]} ~ as wlf'lill a\$*nmlk<D1i':RllmIl:eatdbIl~ em tJllre ~ll11im)Huji'lilllB:imre..fuUtrntrll ~ a local strain of C.tIM:eEalftl1idIJlUv.~rlJi7.'V. w:= s1ll!mlltffllll.. MlJ!.1ciiImnJmiIlllsmfutlmlt~iID!Jll\\'\mt;®lrtniimrdlatlIpjlll5i..'l\,a:tfurr4J.~iimufurtiirn'\, !Ising 10 mE i!1.iI<I:1l1In11llm.,43..15)(( D«J)a:dIs; allIIllil24 !in<OfuII a:JJJliitmw:.h\\GliJIlliilEm <Uifmmtliic mriiiHamM lb:utl;Qniicmriill ~mttrl~ arrdl im mixture in=<N!d ttJIremhem;tt ~:<dtiiwiilljf Ilr& D(Ol.41"<9>.41amdl nll.,(@%" n~N;~. lPl.m!jpiillriic arciiiH att ammmlfiJaljiDll <lit' 20mlilOOlpmrll1!1.It:I!:IrlI!lh:elhJii~Fiier<cli<WlfSi1ill\!~,(Qimk(i)11lbIDr~:mJ.l!1llmtlnafu1W~attlID,wrn·«lllmmll1mtliiDnlimdlnmtrlftmttaUIIl at higher ccocclllll1rnllilllJmS iIIloor~ ttJIremIiwtm1t ~ sfu.m~'